New Flame Retardant Systems Based on Expanded Graphite for Rigid Polyurethane Foams - Anna Strąkowska (Applied Sciences, 2020)
The effect of the addition of new flame retardant systems on the properties of rigid polyurethane (RPUF) foams, in particular, reduction in flammability, was investigated. The modification included the introduction of a flame retardant system containing five parts by weight of expanded graphite (EG) (based on the total weight of polyol), one part by weight of pyrogenic silica (SiO2) and an ionic liquid (IL): 1-ethyl-3-methylimidazolium tetrafluoroborate ([emim] [BF4]), in an amount of 3:1 with respect to the weight of added silica. The kinetics of the synthesis of modified foams—including the growth rate and the maximum temperature—were determined and the physicochemical properties, such as the determination of apparent density and structure by optical microscopy, mechanical properties such as impact strength, compressive strength and, three-point bending test were determined. An important aspect was also to examine the thermal properties such as thermal stability or flammability. It has been shown that for rigid polyurethane foams, the addition of expanded graphite in the presence of silica and ionic liquid has a great influence on the general use properties. All composites were characterized by reduced flammability as well as better mechanical properties, which may contribute to a wider use of rigid polyurethane foams as construction materials.